An evaluation of Surveying (Geomatics) Engineering Teaching Staff’s Perspectives on the Department, Education and the Relationships with Students - Tahsin BOZTOPRAK (Yükseköğretim ve Bilim Dergisi, 2017)
This study is the first of two different studies that were done/are to be done on the department, education, and the relationship between teaching staff and students of the surveying (geomatics) engineering departments in Turkey. As the number of students exceeds the number of teaching staff, the survey study will be longer. For this reason, we wanted to first present the results gained from the survey form applied to teaching staff. A total of 39 faculty members from 13 universities out of 20 universities which have students in the department of Geomatics engineering completed in full the survey forms developed as part of the study. The majority of the teaching staff thought that a sort of chaos was created because the names of the departments differed. They also believed that they mastered the subjects they teach. In addition, they perceived their teaching skills as sufficient, kept the course content up-to-date and found their overall attitude in the classroom to be positive. They thought that they followed the current curriculum and the scientific developments, that they had a good command of the subjects they teach, and that they used convenient assessment and evaluation techniques. The teaching staff considered that they did not avoid being in contact with the students and that they showed sympathy and affinity to them. They also believed that they prepared the exam questions in accordance with the course content. The results obtained from this study will become more meaningful when they are compared to the results from the survey to be conducted/that was conducted with the students.